Development data for cotrol of flow distribution in real time - Добровольська, Оксана Григорівна (Technology audit and production reserves, 2014)
In this article we propose to use the information about the actual rate of discharge on the plumbing network areas for the flow distribution control in real time. The main purpose of research is to develop the algorithm for determining the actual rate of discharge based on pressures measured in separate control nodes. Using of telecommunication modern facilities allows the dispatcher of a communal enterprise to collect and analyze information about the pressures on the network, which comes from the sensors installed in its separate nodes. The article presents a mathematical model that describes the distribution of the flows on the network in real time, the algorithm of software module created on its basis, the results of using of this module for leaks determining on a simplified scheme of the network of one of the residential estates of Zaporizhzhya. The developed algorithm allows to determine the rate of discharge and water leaks locations in real time of pressure measurements in separate nodes. The research results can be used by the controller's services of communal enterprises. We suggest to use information about the actual rate of discharge for the operative redistribution of the flows, finding out the leaks locations and determining of the control nodes locations.